Suffering in Public? Doing Security in Times of Crisis - Briken, Kendra (Social justice, 2011)
The article looks at the nature and evolution of the work of the private security guard, as of 2011. The author discusses the results of her 2009-2010 study of managers and employees at private security companies in Germany. She says the private security industry has expanded sharply in Germany and globally, citing factors including outsourcing. She notes that while security guard has become officially recognized as a profession in Germany, most private security guards continue to face contingent working conditions, with temporary contracts and low wages typical. She analyzes their work in the context of Taylorism, or scientific human resource management, and of the general conditions of service-sector work.